The influence of GDP, population, and net export value on energy consumption. Issue 9 (2nd September 2017) - Huang, Xin; Zhang, Jing; Luo, Ling; Tang, Qiang; Luo, Bing; Zhang, Wei; Deng, Shi-huai; Shen, Fei; Yao, Xue-ping; Xiao, Hong
ABSTRACT: Based on the annual data from 1980 to 2014, the path analysis model was employed to investigate the influence of gross domestic product ( GDP ), total population ( TP ), and net export value ( NEV ) on total energy consumption ( TEC ) in China. The results showed that (1) GDP, influenced 59.73% of TEC, played the most important role to affect TEC . Meanwhile, 37.69% of TEC was directly determined by GDP, and 22.04% of TEC was indirectly influenced by GDP through TP and NEV . (2) TP was the secondary factor to affect TEC ; 6.02% of TEC was directly determined by TP, and 15.20% of TEC was indirectly affected by TP . Moreover, 21.22% of TEC was associated with TP . (3) NEV had the least total effect and the least direct effect on TEC ; 17.24% TEC was influenced by NEV . Among them, 3.58% of TEC was directly determined by NEV, and 13.66% of TEC was indirectly influenced by NEV .